Chaperone-Mediated Autophagy Ablation in Pericytes Reveals New Glioblastoma Prognostic Markers and Efficient Treatment Against Tumor Progression - Molina, María Luisa; García-Bernal, David; Salinas, María Dolores; Rubio, Gonzalo; Aparicio, Pedro; Moraleda, José M.; Martínez, Salvador; Valdor, Rut (Frontiers in Cell and Developmental Biology, 2022)
Background: The lack of knowledge of the progression mechanisms of glioblastoma (GB), the most aggressive brain tumor, contributes to the absence of successful therapeutic strategies. Our team has recently demonstrated a crucial new role for chaperone-mediated autophagy (CMA) in pericytes (PC)-acquired immunosuppressive function, which prevents anti-tumor immune responses and facilitates GB progression. The possible impact that GB-induced CMA in PC has on other functions that might be useful for future GB prognosis/treatment, has not been explored yet. Thus, we proposed to analyze the contribution of CMA to other GB-induced changes in PC biology and determine if CMA ablation in PC is a key target mechanism for GB treatment. Methods: Studies of RNA-seq and secretome analysis were done in GB-conditioned PC with and without CMA (from knockout mice for LAMP-2A) and compared to control PC. Different therapeutic strategies in a GB mouse model were compared. Results: We found several gene expression pathways enriched in LAMP2A-KO PC and affected by GB-induced CMA in PC that correlate with our previous findings. Phagosome formation, cellular senescence, focal adhesion and the effector function to promote anti-tumor immune responses were the most affected pathways, revealing a transcriptomic profiling of specific target functions useful for future therapies. In addition, several molecules associated with tumor mechanisms and related to tumor immune responses such as gelsolin, periostin, osteopontin, lumican and vitamin D, were identified in the PC secretome dependent on GB-induced CMA. The CMA ablation in PC with GB cells showed an expected immunogenic phenotype able to phagocyte GB cells and a key strategy to develop future therapeutic strategies against GB tumor progression. A novel intravenous therapy using exofucosylated CMA-deficient PC was efficient to make PC reach the tumor niche and facilitate tumor elimination. Conclusion: Our results corroborate previous findings on the impaired immunogenic function of PC with GB-induced CMA, driving to other altered PC functions and the identifications of new target markers related to the tumor immune responses and useful for GB prognosis/therapy. Our work demonstrates CMA ablation in PC as a key target mechanism to develop a successful therapy against GB progression.